2006
DOI: 10.1158/1078-0432.ccr-05-2721
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Irradiation Induces Vascular Endothelial Growth Factor and Promotes Growth of Hepatoma Cells: Implications for Radiotherapy of Hepatocellular Carcinoma

Abstract: Purpose: To investigate the clinical benefit of additional radiotherapy to patients with unresectable hepatocellular carcinoma treated with transcatheter arterial chemoembolization (TACE) and the molecular effects of radiation on gene expression in hepatoma cells. Experimental Design: Between August 1996 and August 2003, 276 and 64 patients with American Joint Committee on Cancer stage T 3 N 0 M 0 hepatocellular carcinoma receiving TACE alone andTACE followed by three-dimensional conformal radiotherapy, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 42 publications
4
49
1
Order By: Relevance
“…Overexpression of VEGF, an important growth factor controlling angiogenesis, has been associated with tumor progression, metastasis, and reduced survival in neuroblastoma and other tumors (15)(16)(17)(18). The induction of VEGF in tumor cells by irradiation has been previously reported (19)(20)(21). In keeping with these reports, we found an upregulation of the VEGF mRNA transcript and protein after irradiation in neuroblastoma cells analysed.…”
Section: Discussionsupporting
confidence: 88%
“…Overexpression of VEGF, an important growth factor controlling angiogenesis, has been associated with tumor progression, metastasis, and reduced survival in neuroblastoma and other tumors (15)(16)(17)(18). The induction of VEGF in tumor cells by irradiation has been previously reported (19)(20)(21). In keeping with these reports, we found an upregulation of the VEGF mRNA transcript and protein after irradiation in neuroblastoma cells analysed.…”
Section: Discussionsupporting
confidence: 88%
“…34,35 Thus, such high-risk patients may benefit from concomitant systemic therapy such as novel agents to block multimolecular pathways. [35][36][37] This study has several limitations. First, quantitative assessments of changes in maximal tumor SUV from baseline after completion of chemoradiotherapy were not performed.…”
Section: Discussionmentioning
confidence: 96%
“…Because of the existence of early intrahepatic recurrence with vascular endothelial growth factor increment after successful local RT [26], there is an expectation that the combination of a targeted agent like sorafenib concurrently and/or sequentially could be synergistic. Chen et al [27] reported results of a phase 2 study evaluating the efficacy of an RT and sorafenib combination, and the treatment showed a 55% objective response rate with a 32% 2-year overall survival rate.…”
Section: Considerations For Rt Applicationmentioning
confidence: 99%